The Effect of Traditional Market Relocation on Traders' Income - Sartika, Dewi; Abidin, Zaenal; Nilfatri, Nilfatri (Zabags International Journal of Economy, 2024)
This research aims to determine and analyze the magnitude of the influence of the relocation of the traditional market in Muara Sabak Barat District on traders' income. This research uses a quantitative approach and data analysis. The data analysis used is simple linear regression analysis, T test, and coefficient of determination (R²). The samples used were 110 traders with 30 samples for trials and 80 samples for research. The results of the research are that relocation has a positive effect on traders' income in the Muara Sabak Barat sub-district market. A significant value of 0.00 was obtained which was smaller than 0.05 and the calculated t value was 3.675 which was greater than the t table of 1.990. Based on the coefficient of determination test, the R square (R²) result was 0.148, this means that 14.8% of the income variable can be explained by the relocation variable in this research, while the remaining 85.2% is a variable outside this research. So, it can be concluded that Ho is rejected and Ha is accepted, which means that traditional market relocation has an influence on the income of traditional market traders in Muara Sabak Barat subdistrict with the income variable being influenced by relocation by 14.8%, the remaining 85.2% is influenced by other factors outside this research.